Trends in rape cases in a Nigerian state - Idoko, Chinedu A (Afr Health Sci, 2020)
BACKGROUND: Rape remains a controversial issue with a few victims reporting experience because of the myriad of societal perception, prolonged steps in pursuing a case to logical conclusion of securing conviction, as well as psychological and physical residuals of the experience. Data in Nigeria is therefore hard to come by as it is diminished and often not available. OBJECTIVES: To assess the pattern and trend of rape cases in a State in Nigeria. METHODS: A descriptive and retrospective study where data records on socio-demographics and case specifics was collected on victims of sexual assault that reported to DFID/ PATHS 2 supported Tamar Sexual Assault Centre between 2014 and 2016 after which it was analysed and presented in bar charts. RESULT: The yearly prevalence varied for the different age groups studied with the highest prevalence noted for 13 years and above (175,200,255) over the 3 years of 2014, 2015 and 2016 studied. The reported cases also improved over the studied years with rates of 0.47, 0.96 and 0.5 respectively. CONCLUSION: The yearly comparison and baseline data show that the centre's establishment caused an improvement in rape case reporting and follow-up.